PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN KOLABORASI PESERTA DIDIK KELAS III SDN 013 PASIRKALIKI BANDUNG - Siti Humaeroh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Based on the results of observations made in class III at SDN 013 Pasirkaliki Bandung, problems related to learning were found, one of which was collaboration skills. This can be seen when learning is carried out in groups, there are some students who are not actively involved in discussions, lack of cooperation, work on assignments individually, and do not respect friends in discussions, this shows that collaboration skills students are still low. This study aims to improve students' collaboration skills in class III SDN 013 Pasirkaliki Bandung by using the Project Based Learning learning model. This research is a Classroom Action Research. The research subjects were class III students for the 2022/2023 academic year, totaling 28 students. Data collection techniques using observation sheets and documentation. The results of the study show that the implementation of learning using the Project Based Learning learning model can increase student collaboration. This can be seen from the results of the percentage of student collaboration in cycle I initially at 42.86%, then increased to 60.71% in cycle II so that it experienced an increase of 17.85%, collaboration skills including the medium category. Then in cycle III a percentage of 85.71% was obtained so that there was an increase of 25% from cycle II, students' collaboration skills were included in the high category. The results of observations of classroom action research that have been carried out, it can be concluded that the application of the Project Based Learning learning model can improve students' collaboration skills.